2023
DOI: 10.3389/fvets.2023.1127117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sea buckthorn extract on production performance, serum biochemical indexes, egg quality, and cholesterol deposition of laying ducks

Abstract: The purpose of this experiment was to study the effect of sea buckthorn extract (SBE) supplementation on the production performance, serum biochemical indexes, egg quality, and cholesterol deposition of laying ducks. A total of 240 23-week-old laying ducks (female ducks) with similar body weight were randomly divided into four treatment groups with 6 replicates of 10 each. The experimental groups were fed diets supplemented with 0, 0.5, 1.0, and 1.5 g/kg of SBE, respectively. The results showed that the additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Yao et al . discovered that the administration of sea buckthorn extract resulted in a notable elevation in serum immunoglobulin levels, specifically IgA, IgM, and IgG, among female ducks 43 . Our study findings demonstrated that the administration of quercetin alone or in combination with genistein had a synergistic effect in enhancing the levels of IgA and IgM in the serum of laying hens.…”
Section: Discussionsupporting
confidence: 51%
“…Yao et al . discovered that the administration of sea buckthorn extract resulted in a notable elevation in serum immunoglobulin levels, specifically IgA, IgM, and IgG, among female ducks 43 . Our study findings demonstrated that the administration of quercetin alone or in combination with genistein had a synergistic effect in enhancing the levels of IgA and IgM in the serum of laying hens.…”
Section: Discussionsupporting
confidence: 51%
“…Elevated egg weight typically indicates improved egg quality [14]. Prior research has demonstrated that incorporating certain organic substances can enhance the feed utilization, consequently improving the egg quality [15]. This could explain why the highyielding group in this experiment exhibited superior feed utilization, resulting in higher egg weights.…”
Section: Differences Between Egg Quality In High-and Low-egg-producti...mentioning
confidence: 75%
“…No studies were found investigating the effect of mixture of sea buckthorn meal and bilberry leaves. When supplementing alone, sea buckthorn extracts (0.5, 1.0, and 1.5 g/kg) diets reduced the levels of serum total cholesterol, triglyceride, and low-density lipoprotein cholesterol, compared to the control in laying ducks (Yao et al, 2023). Contrary, Orczewska-Dudek et al, (2018) showed a reduction of triglyceride, cholesterol and glucose content in plasma from the chickens receiving sea buckthorn meal in the diet (dietary 3% flax oil and 3% dried sea buckthorn pomace).…”
Section: Growth Performancementioning
confidence: 93%